Substrate Selection for Full Exploitation of Organic Semiconductor Films: Epitaxial Rubrene on β‐Alanine Single Crystals. Issue 18 (1st October 2015) - Trabattoni, Silvia; Raimondo, Luisa; Campione, Marcello; Braga, Daniele; Holmberg, Vincent C.; Norris, David J.; Moret, Massimo; Ciavatti, Andrea; Fraboni, Beatrice; Sassella, Adele
Abstract : Rubrene (RUB) is one of the most studied organic semiconductors because, in the orthorhombic single‐crystal phase, it exhibits a record exciton diffusion length and one of the highest charge carrier mobilities ever reported. Here, thin films of oriented crystalline RUB are successfully grown in vacuum on millimeter‐sized (010)‐β‐alanine (β‐ala) single crystals with a step‐growth protocol, exploiting organic epitaxy. The experimental characterization demonstrates that these RUB films grow in the orthorhombic polymorph with the (100)RUB plane in contact with the (010)β‐ala surface and with precise azimuthal orientations. A complementary study of the RUB(100)/β‐ala(010) interface, performed by computational simulations, confirms the epitaxial relations expected by considering the molecular scale corrugations of the surfaces. Moreover, thanks to the wide transparency region of β‐ala, the RUB absorption bands in the UV range are directly detected for the first time. Finally, removal of the water‐soluble substrate enables the integration of the films in field effect transistors as high quality active organic layers. The characteristics of such RUB‐based devices confirm the quality and versatility of epitaxial thin films for use in organic electronics. Abstract : β‐alanine(010) single crystals are selected as an appropriate substrate to grow millimeter‐sized, orthorhombic rubrene (RUB) (100) crystalline films exploiting organic epitaxy. The water solubility of β‐alanine substrate and the high crystalline quality of RUB thin films allow for the wet‐transfer of the semiconductor overlayer onto Cytop and the fabrication of working organic field effect transistor.